Impact of the 1988 Basle Accord on International Banks. - Wagster, John D (Journal of Finance, 1996)
The ostensible purpose of the Basle Accord was to standardize bank-capital regulations among the twelve leading industrial countries. Its ulterior goal was to 'level the playing field' by eliminating a funding-cost advantage of Japanese banks that had allowed them to capture more than one-third of international lending. The wealth gain for Japanese bank shareholders was 31.63 percent. Wealth effects for shareholders of non-Japanese banks were not significant. These results suggest that the Baste Accord did not eliminate the pricing advantage of Japanese banks, challenging the non-Japanese regulators' contention that the regulation would help level the playing field.